2016
DOI: 10.1016/bs.aiip.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito Peptide Hormones

Abstract: Mosquitoes, like other insects, produce a diversity of peptide hormones that are processed from different precursor proteins and have a range of activities. Early studies relied on purification of bioactive peptides for hormone identification, but more recently genomic data have provided the information needed to more comprehensively identify peptide hormone genes and associated receptors. The first part of this chapter summarizes the known or predicted peptide hormones that are produced by mosquitoes. The sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 205 publications
(381 reference statements)
0
14
0
Order By: Relevance
“…Future work regarding potential effects of ABA on A. stephensi larval feeding behavior could focus on sulfakinin and neuropeptide F, both of which modulate feeding behavior in D. melanogaster larvae (Söderberg et al, 2012;Fadda et al, 2019). Both neuropeptides are also known to be conserved in A. gambiae (Strand et al, 2016) and are represented as orthologs in A. stephensi 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Future work regarding potential effects of ABA on A. stephensi larval feeding behavior could focus on sulfakinin and neuropeptide F, both of which modulate feeding behavior in D. melanogaster larvae (Söderberg et al, 2012;Fadda et al, 2019). Both neuropeptides are also known to be conserved in A. gambiae (Strand et al, 2016) and are represented as orthologs in A. stephensi 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple endocrine factors including JH, ILPs, OEH, and 20E coordinate each gonadotrophic cycle (Klowden, 1997; Roy et al. , 2016; Strand et al. , 2016; Zhu & Noriega, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Previous results indicated that the 8 residue AKH was metabolically active in sugar‐fed female Anopheles gambiae but not the 10 amino acid peptide, which was subsequently identified to be an AKH/corazonin peptide (Kaufmann & Brown, 2006, 2008; Strand et al. , 2016). For this study, the 8‐residue Ae.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been many studies and reviews regarding insect hormones. Peptide hormone genes and their receptors in insects have been reviewed previously (Riehle et al, 2002;Reiher et al, 2011;Wegener and Veenstra, 2015;Strand et al, 2016). Although there have been several reviews on hormones produced by the intestinal endocrine cells (Wegener and Veenstra, 2015), the most recent literatures has not yet been summarized.…”
mentioning
confidence: 99%